Prototype Monitoring of IoT-based Laboratory Firefighting System - Cahyadi, Setiaji; Karman, Joni; Alamsyah, Muhammad Nur (Building of Informatics, Technology and Science (BITS), 2021)
The problem in this study is the absence of automatic firefighters that helps performance on 24-hour safeguards so that it is very susceptible to a short circuit or electrical relations that lead to fires that cause enormous losses both material and immaterial. This research uses the prototype method. The results showed that the planning of making hardware and software regarding planning fire extinguishers using the Arduino Uno board and a fire sensor or flame sensor and a gas sensor or MQ2 Sensor as a foundation where the hardware can be input on the Arduino IDE software and connected to WiFi ESP2866 as a IoT controller and control the room in 24 hours because this tool has a buzzer so that if there is a fire and smoke detected can turn on the sensor and the arm arises, the warning will be a fire hazard.